Sigurado Ka Na Ba? Exploring Career Uncertainty in Filipino College Students - Mattison, Hiyasmin Cariño (Philippine Social Sciences Review, 2011)
The study attempted to identify factors affecting career uncertainty as perceived by college students in a university in the Philippines. One hundred thirteen students responded to a brief free-response questionnaire in which they were asked to describe experiences that have led to them being either certain or uncertain about their future careers, their feelings resulting from certainty or uncertainty, and either supportive actions towards certainty or coping mechanisms employed during uncertainty. The data were transcribed and coded into themes based on Social Cognitive Career Theory (SCCT). Follow-up interviews were conducted with volunteer participants to validate questionnaire data. Results suggest that career uncertainty may be influenced more by outcome expectations (such as expectation of finding a high-paying job) rather than self efficacy or other contextual supports and barriers (such as parental pressure). The data also suggest that information and guidance received prior to the collegiate years may be an influential factor in career uncertainty. Suggestions for career guidance for college students and future research into the utility of SCCT in the Filipino context are made.
Keywords: uncertainty, college students, career, Filipino